Feeding and eating problems in children and adolescents with autism: A scoping review - Baraskewich, Jessica (Autism, 2021)
Feeding problems, such as picky eating and food avoidance, are common in youth with autism. Other feeding and eating problems (e.g. disordered eating, fear of trying new foods, and insistence on specific food presentation) are also common in this population. This scoping review describes the nature and extent of feeding and eating problems in autistic youth and reports characteristics of autistic youth who experience such issues. Thirty-four studies were included in the current review, with almost all studies (91%) investigating feeding problems. Only 9% of studies examined concern with weight, shape, and/or body image, but several authors noted that disordered eating attitudes and behaviors may occur more frequently in those with autism than their peers without autism. No common individual characteristics (e.g. cognitive functioning and autism symptom severity) were identified for youth who experience feeding or eating problems. Although differentiating “feeding” from “eating” problems is critical for accurate identification and treatment of these issues, the existing literature has failed to do so. We propose that in future research “eating problems” be used when behaviors involve preoccupation with food, eating, or body image, and “feeding problems” be used when such preoccupation is absent. LAY ABSTRACT: Feeding problems, such as picky eating and food avoidance, are common in youth with autism. Other, broader difficulties with feeding and eating (eating disorder symptoms such as restricting food intake or preoccupation with body shape or weight and insistence on specific food presentation) are also common in autistic individuals. Here, we describe the nature and extent of feeding and eating problems in youth with autism. We found no common characteristics (such as severity of autism symptoms) that best describe autistic youth who experience problems with feeding or eating. Almost all studies we reviewed focused on problems with feeding (selective or picky eating), and only a few studies focused on eating disorder symptoms (concern with weight, shape, and/or body image). However, some researchers reported that eating disorder symptoms may occur more often in autistic individuals compared to their peers without autism. Many studies used the terms “feeding” and “eating” problems interchangeably, but understanding the difference between these problems is important for researchers to be consistent, as well as for proper identification and treatment. We suggest future researchers use “eating problems” when behaviors involve preoccupation with food, eating, or body image, and “feeding problems” when this preoccupation is absent. We highlight the importance of understanding whether feeding or eating problems are separate from autism traits, and the role of caregivers and other adults in the child’s treatment. Considerations for health-care providers to assist with diagnosis and treatment are also provided.